Co-Administration of ACLAS in Health Services: The Case of Huanuco Region - Montes Gómez, Jamira Berenice (2020)
Objective. To analyze the involvement of Local Community Health Administration Associations (ACLAS) of Regional Government of Huánuco. Methods. Descriptive study with the application of questionnaires (quantitative method). Research population comprised members involved in the co-administration (General Assembly, Board of Directors and Management) of the 60 ACLAS in force, jurisdictionally belonging to the Huánuco Executing Unit, 2017 and the sample comprised 132 members belonging to 22 current ACLAS. Results. A positive relationship was found between co-administration and management of health services, with human resources (0.53) and the exercise of administrative functions (0.43) having the greatest relationship with management. In the same way, the lack of commitment of the local authorities of the Board of Directors for planning of the work of the ACLAS or to facilitate the processes of programming activities of the Local Health Plan (PSL) are highlighted in the study. Conclusion. The research identifies the factors of human resource management, such as the insufficient number of health personnel to care for users. In addition, the lack of training and technical assistance for them in direct relation to the health management of health facilities.